Numerical studies of shear-thinning droplet formation in a microfluidic T-junction using two-phase level-set method - Wong, Voon Loong; Loizou, Katerina; Lau, Phei-Li; Graham, Richard Stuart; Hewakandamby, Buddhika N. (Elsevier, 2017)
A conservative level-set method (LSM) embedded in a computational fluid dynamics (CFD) simulation provides a useful approach for the studying the physics and underlying mechanism in two-phase flow. Detailed two-dimensional (2D) computational microfluidics flow simulations have been carried out to examine systematically the influence of different controlling parameters such as flow rates, viscosities, surface wettability, and interfacial tensions between two immiscible fluids on the non-Newtonian shear-thinning microdroplets generation process. For the two-phase flow system that neglects the Marangoni effect, the breakup process of shear-thinning microdroplets in cross-flowing immiscible liquids in a microfluidic device with a T-shaped geometry was predicted. Data for the rheological and physical properties of fluids obeying Carreau-Yasuda stress model were empirically obtained to support the computational work. The simulation results show that the relevant control parameters mentioned above have a strong impact on the size of shear-thinning droplets generated. Present computational studies on the role and relative importance of controlling parameters can be established as a conceptual framework of the non-Newtonian droplet generation process and relevant phenomena for future studies.